Coaching for leadership : writings on leadership from the world's greatest coaches - .; Goldsmith, Marshall; Lyons, Laurence; McArthur, Sarah (San Francisco, CA : Jossey-Bass, 2012)
"Today's coaches are challenged with the recurring task of weaving threads from several disciplines into a tapestry that is fit for purpose in helping their clients learn and succeed. In this sense, the coach has to become a discriminating eclectic, developing a keen sense of judgment to select which threads are best woven into the fabric and those that it would be better to simply throw away. Coaching for Leadership is intended to be a cherished companion in that learning journey presented by the world's greatest coaches, including: Marshall Goldsmith, Paul Hersey, Beverly Kay, David Ulrich and many more"--
Includes bibliographical references and index.
Keywords: Executives -- Training of; Leadership -- Study and teaching; Mentoring in business; Business consultants; BUSINESS & ECONOMICS / Human Resources & Personnel Management